God's Vision and Faith as the Basis of the Effectiveness of a Church Leader's Ministry - Catur Saputra; Nuh Gosianes; Makhtar N’diaye; Renita Septiani; Djone Georges Nicolas (PT FORMOSA CENDEKIA GLOBAL, 2022)
The purpose of this study was to analyze God's vision and faith as the basis for the effectiveness of a church leader's ministry, using a qualitative method approach by collecting data from books, journals and interviews. First, the point of the ministry of church leaders is the fruit of God's vision and firm faith that the leader has received. A leader is essentially a visionary because the concept is the foundation of every plan to achieve goals or targets. However, it has been suspect that some Christian leaders, especially in the Church, do not have a clear vision, causing the implementation of services in the Church to be less effective. In conclusion, the effectiveness of ministry for a leader in the Church is greatly influenced by the collective vision and faith because they are one unity and the grace of God to support the Church.